CORRELATION OF KNOWLEDGE LEVELS ABOUT MENARCHE WITH READINESS FOR THE MENARCHE INSTUDENTS CLASS V AND VI IN SD NEGERI 2 JAMBIDAN BANTUL YOGYAKARTA - Wahyuni, Wahyuni; Utami Lubis, Dina Putri (Jurnal Kesehatan Samodra Ilmu (JKSI), 2021)
ABSTRACT Background: Menarche (first menstruation) is the first menstruation that occurs in the uterine wall and is known a menstruation. The arrival of Menarche has a problem to discuss psychological problems in young women, they need to get information about menarche to have good knowledge and have good preparedness in the conversation that the arrival of menarche. Objective: this study aims to determine the relationship of the level of knowledge about menarche with the readiness to has menarche in class V and VI students at SD Negeri 2 Jambidan Bantul Yogyakarta.Method: The research design used was descriptive correlational with cross sectional approach. The technique used in this study is total sampling with a total sample of 37 peoples.Results: Most respondents had a good level of knowledge of 26 peoples (70.3%) and preparedness to has menarche in the category of ready 34 peoples (91.9%). When using Kendall Tau correlation analysis with a correlation coefficient of 0.783 and the results obtained p value <α (0,000 <0.05).Conclusion: There is a significant relationship between the level of Knowledge About Menarche and Menarche's Readiness in Class V and VI Students at SD Negeri 2 Jambidan Bantul Yogyakarta.